Silicon Carbide One-dimensional Nanostructures - Latu-Romain, Laurence, 1980-; Ollivier, Maelig (Focus series., 2015)
One-dimensional (1D) nanostructures from silicon carbide (SiC) are attracting the scientific community because their combination of excellent intrinsic properties with low dimensionality has tremendous potential for breakthrough applications. Silicon carbide does indeed possess very interesting physicochemical and electronic properties, particularly in its biocompatibility. 1D nanostructures such as nanowires and nanotubes are remarkable due to their high surface area relative to their volume, as well as their unique characteristics in comparison to those of bulk materials. Dedicated to SiC-